The pharmacoeconomic assessment of the rationality of the use of memantine and its combinations with acetylcholinesterase inhibitors in the treatment of dementia in Alzheimer’s disease in Ukraine - Fedotova, M. S.; Panfilova, H. L.; Tereshchenko, L. V.; Velia, M. I.; Korzh, Iu. V. (Social Pharmacy in Health Care, 2024)
Aim. To conduct the pharmacoeconomic assessment of the rationality of using memantine and its combinations with acetylcholinesterase inhibitors in the treatment of dementia in Alzheimer’s disease in Ukraine. Materials and methods. Historical, analytical and comparative, systematic, graphic, logical, hypothetical-deductive, as well as marketing, pharmacoeconomic, and mathematical and statistical methods of analysis were used. The pharmacoeconomic studies were conducted using the cost-effectiveness method. CER and ICER indicators were calculated for dementia treatment regimens in Alzheimer’s disease containing memantine and its combinations with acetylcholinesterase inhibitors (donepezil, galantamine, rivastigmine) in the period of 12 and 24 weeks of their use. The pharmacoeconomic analysis used data on the clinical effectiveness of dementia treatment regimens in Alzheimer’s disease presented in the Sochrane library (ID Number: CN-01071444; Accession Number: PUBMED 25932260e). Results. It was found that despite the clinical advantages of using the memantine+galantamine regimen proven by scientists according to the MMSE scale, the use of the memantine+rivastigmine regimen seemed to be rational (CER1 = 23.13 and CER2 = 34.57 USD/unit of increased efficiency). The clinical and economic benefits of using the memantine+galantamine regimen in the treatment of dementia patients with Alzheimer’s disease were proven in the 12- and 24-week regimen (MMSE scale). In the case of using the AADL scale, it was rational, from the point of view of economical use of resources, in the 12-week regimen of treating patients, the use of the memantine + rivastigmine regimen was less expensive (CER1 = 18.30 $/unit of AADL score reduction), while in the 24-week regime it was the memantine + placebo regimen (CER2 = $37.58 $/ unit of AADL score reduction). Conclusions. The research results presented can be used in forming drug purchases carried out by specialized healthcare institutions under the conditions of limited budget funding and growing needs of psychoneurological patients in effective medical and pharmaceutical care.